Simulasi Penggerak Roda Motor Sinkron Permanen Magnet Untuk Membuktikan Kesesuaian Super Kapasitor Dalam Kendaraan Listrik Hibrida (Hybrid Electric Vehicle – Hev) Menggunakan Plecs (Matlab/Simulink) - Sugeng Purwanto (Sutet, 2018)
In the framework of the development of a drive system used for propulsion in a hybrid electric vehicle (HEV), a 16-pole permanent magnet (PM) synchronous in wheel motor is used. HEV wheel motor system is designed to convert electrical power into mechanical torque on the wheel using AC voltage as a voltage source and supercapacitor as an energy storage, two level IGBT’s voltage source converters, and permanent magnet synchronous motor (PMSM). The purpose of this research is to simulate the suitability of 3300 µF capacitors in HEV systems with PLECS based on MATLAB / SIMULINK. The design of current controller, speed controller and HEV electrical model are discussed as components of a drive control. All components used in this study use predetermined data and parameters. The voltage, current and angular velocity of HEV wheel motors output were recorded. The simulation results show that with a constant current, the speed will decrease and the capacitor voltage will increase. PMSM is changed as a generator that stores electric current to super capacitors, which can store more energy with a short time to be charged. In this case it can be concluded that super capacitors are very suitable to be used in this system.